From Theory of Mind to Epistemic Cognition. A Lifespan perspective - Iordanou, Kalypso (Frontline Learning Research, 2017)
Although a sizeable body of research now exists in epistemic cognition, it tends to stand apart to other aspects of cognition and cognitive development. Here it is proposed situating epistemic cognition in a context of its roots and development as a dimension of cognitive development more generally. The present paper draws a strong continuous link between the earliest understanding of other minds, examined under the Theory of Mind, and the tasks that confront adults throughout the lifespan – that of interpreting evidence and coordinating it with what they already take to be true. The primary focus is the How question of knowledge change. To gain insight into this question, it is proposed focusing on epistemic activity in action. It is suggested here that the standards for knowledge formation and revision, which are closely connected with epistemic understanding of theory-evidence coordination, change developmentally. Another major change, proposed, is that the process increasingly comes under conscious control.